Using the RE-AIM framework to evaluate internal and external validity of mobile phone–based interventions in diabetes self-management education and support. (7th May 2020) - Yoshida, Yilin; Patil, Sonal J; Brownson, Ross C; Boren, Suzanne A; Kim, Min; Dobson, Rosie; Waki, Kayo; Greenwood, Deborah A; Torbjørnsen, Astrid; Ramachandran, Ambady; Masi, Christopher; Fonseca, Vivian A; et al.
Abstract: Objective: We evaluated the extent to which studies that tested short message service (SMS)– and application (app)-based interventions for diabetes self-management education and support (DSMES) report on factors that inform both internal and external validity as measured by the RE-AIM (Reach, Efficacy/Effectiveness, Adoption, Implementation, and Maintenance) framework. Materials and Methods: We systematically searched PubMed, Embase, Web of Science, CINAHL (Cumulative Index of Nursing and Allied Health Literature), and IEEE Xplore Digital Library for articles from January 1, 2009, to February 28, 2019. We carried out a multistage screening process followed by email communications with study authors for missing or discrepant information. Two independent coders coded eligible articles using a 23-item validated data extraction tool based on the RE-AIM framework. Results: Twenty studies (21 articles) were included in the analysis. The comprehensiveness of reporting on the RE-AIM criteria across the SMS- and app-based DSMES studies was low. With respect to internal validity, most interventions were well described and primary clinical or behavioral outcomes were measured and reported. However, gaps exist in areas of attrition, measures of potential negative outcomes, the extent to which the protocol was delivered as intended, and description on delivery agents. Likewise, we found limited information on external validity indicators across adoption, implementation, and maintenance domains. Conclusions: Reporting gaps were found in internal validity but more so in external validity in the current SMS- and app-based DSMES literature. Because most studies in this review were efficacy studies, the generalizability of these interventions cannot be determined. Future research should adopt the RE-AIM dimensions to improve the quality of reporting and enhance the likelihood of translating research to practice.